Penerapan dan Penyimpangan Maksim Kerja Sama Grice dalam Podcast Sule Bersama Rizwan Media Sosial Youtube: Analisis Pragmatik - Dinar Thahira Handatika; Farida Yufarlina Rosita; Berlian Pancarrani (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the application and deviation of conversational maxims in Grice's cooperative theory in the podcast